Philosophy Of Mathematics And Mathematics Education - zulhendri; Jamaris (CV. AFDIFAL MAJU BERKAH, 2021)
Philosophy of mathematics is a branch of philosophy that studies philosophical assumptions, foundations, and effects of mathematics. The aim of the philosophy of mathematics is to provide a record of the nature and methodology of mathematics and to understand the place of mathematics in human life. The field of knowledge called the philosophy of mathematics is the result of philosophical thought whose goal is mathematics itself. The main concern of the philosophy of mathematics is to provide an explanation of the nature of mathematics. While the philosophy of mathematics education is a philosophy that discusses the process of mathematics education. Mathematics education refers to the problem of learning and teaching. The philosophy of mathematics forms the philosophy of mathematics education, meaning that the philosophy of mathematics education is supported by the philosophy of mathematics. Towards learning in mathematics education, philosophical thought has a very important role. Philosophy also plays a role in creating a mathematics learning that allows students to build their logical thinking and build their mathematical knowledge. The philosophy of mathematics forms mathematics education, meaning that mathematics education is supported by the philosophy of mathematics. Thus, Philosophy of mathematics is a branch of philosophy that studies philosophical assumptions, foundations, and effects of mathematics. The aim of the philosophy of mathematics is to provide a record of the nature and methodology of mathematics and to understand the role of mathematics in human life.